Implementation of the Food Estate Program from the Perspective of Spatial Planning and Environmental Law in Indonesia - putri febrianty, shalsabila; Nugroho, Wahyu (Faculty of Law, Mulawarman University, 2025)
The food estate program initiated by the government since the new order era until now has experienced dynamics in its implementation. In various periods, this program often has negative impacts on the environment, ranging from the conversion of forest land, damage to peat ecosystems, to agrarian conflicts with local communities. In the modern era, the implementation of the food estate still faces the same challenges, especially in terms of spatial planning law and environmental sustainability, which have drawn criticism from various parties. However, the government has also shown an adaptive response to this failure by designing various improvement efforts. Through land suitability evaluation, infrastructure optimization, empowerment of local farmers, and the application of the Social-Ecological System (SES) approach, the government is trying to realize more sustainable food governance and maintain national food security.